Transformation of the Spread of Islamic Messages through the Transition from Traditional Media to Digital Media in Contemporary Da'wah - Aditia, Rafinita; Hafizah, Evi (Program Studi Komunikasi dan Penyiaran Islan STAIMAS Wonogiri, 2024)
This study discusses the transformation of Islamic da'wah from traditional media to digital media and its impact on the spread of Islamic messages in the contemporary era. With the development of information and communication technology, da'wah is no longer limited to conventional methods such as face-to-face lectures and book publishing, but now involves the use of digital media, such as social media, instant messaging applications, and video streaming platforms. This study uses literature study methodology and comparative analysis to evaluate the differences between the dissemination of Islamic messages through traditional media and digital media, focusing on aspects of audience reach, interaction, and the quality and effectiveness of the messages conveyed. The results of the study indicate that the use of digital media in da'wah significantly expands the reach of Islamic messages, allowing for faster and wider dissemination to a more diverse audience. Digital media also increases interaction between preachers and audiences through comment features, live streaming, and question and answer sessions, creating a more dynamic two-way dialogue. However, this study also highlights the challenges faced, including the potential for message distortion and the need for digital literacy among preachers to ensure the authenticity and accuracy of the information conveyed. By combining traditional and digital media approaches holistically, da'wah can be more relevant, inclusive, and adaptive in responding to the challenges of the times and the spiritual needs of modern society.